Use of Individualized Learning Plans to Facilitate Feedback Among Medical Students. Issue 4 (7th August 2020) - Kiger, Michelle E.; Riley, Caylin; Stolfi, Adrienne; Morrison, Stephanie; Burke, Ann; Lockspeiser, Tai
Abstract: Theory: Self-regulated learning theory suggests that individualized learning plans can benefit medical trainees by providing a structured means of goal setting, self-monitoring, and self-evaluation. External feedback also plays an important role in affecting learner motivations, perceptions, and self-evaluations. Accordingly, having learners share individualized learning plans with preceptors might promote self-regulated learning by helping align the feedback they receive with their learning goals. Hypothesis : We hypothesized having medical students share individualized learning plans with attendings and residents would improve the quality of the feedback they received, increase the likelihood that feedback correlated to their learning goals, and improve their perceptions of feedback received. Method : In this multisite study, third-year medical students on their pediatric clerkship created individualized learning plans and shared them with residents and attendings by writing a learning goal on at least one of their required faculty feedback forms. The quality of feedback on forms with versus without a learning goal written on top was scored using a validated scoring tool and compared using a Wilcoxon signed-ranks test, and the frequency with which feedback directly correlated to a student learning goal on forms with versus without a learning goal written on top was compared using a chi-square test. Students completed a post-clerkship survey rating the quality of feedback and teaching they received, perceptions of the individualized learning plans, progress toward achieving learning goals, and whether or not they received teaching and/or feedback related to learning goals. Results : Thirty-six students completed a total of 108 learning goals and 181 feedback forms, of which 42 forms (23.2%) had a learning goal written on top. The mean ( SD ) feedback score between forms with [3.9 (0.9)] versus without [3.6 (0.6)] a learning goal written on top was not different ( p = .113). Feedback on forms with a learning goal written on top was more likely to correlate to a student learning goal than feedback on forms without a learning goal (92.9% vs 23.0% respectively, p < .001). Student perceptions of the usefulness of learning goals did not differ between students who reported receiving teaching or feedback related to a learning goal and those who did not. Conclusions : Sharing individualized learning plans with preceptors helped align feedback with learning goals but did not affect the quality of feedback. Further research should examine the bidirectional relationship between individualized learning plans and feedback in light of other contextual and interpersonal factors.